The el cucayo fund, a two-dimensional analysis: as immigration policy and as an experience of entrepreneurship and individual investments - Sandoval Gallegos, Angélica María; López Salazar, José Luis (mktDESCUBRE; Vol 1 No Edición Es (2024): 7th International Scientific Congress of Administrative and Financial Sciences FADE 2023, 2024)
This study analyzes the effects on the migratory experience and labor trajectory in the country of destination as determinants for the productivity of the businesses undertaken and if this influences the sustainability of the migrant and their families in origin. To respond to a comprehensive vision that encompasses the multiple sides of the phenomenon of return. Based on the program Fondo Concursable El Cucayo implemented by the National Secretariat for Migrants (SENAMI) from 2008 to 2012, a program that was based on a reinsertion policy for Ecuadorian migrant returnees through entrepreneurship projects. The results of the research have shown that these life experiences at the destination do indeed condition productivity but do not guarantee the migrant's sustainability.